The Analysis of Extended Technology Acceptance Model to Understand use of Platform at Education Technology Startup - Heru Wijayanto Aripradono (Sistemasi: Jurnal Sistem Informasi, 2023)
The growth of startups in Indonesia Education Technology (EdTech) has increased significantly and related with the growth of EdTech globally. Related to the pandemic and the need for future skills, it is a moment for EdTech startups, to build a process, approach and strategy for teaching-learning activities to be able to produce someone with the skills needed in the future. The purpose of this research is to see how the technology-based learning process in EdTech startups can be used and adapted by users in improving their skills and needs in the future. This research uses the Technology Acceptance Model (TAM) framework by adding facilitating condition variables as extended factors to see how the user's environmental conditions help encourage and adapt the use of technology. This research uses a quantitative method where data collection is carried out to students who are still active in EdTech startups Indonesia in the period 2016 - 2022 and analyzed using structural equation modeling. The results illustrate that TAM has been able to explain the factors that predict the use of e-learning among users on the Edtech Startup platform in supporting the learning process. Then there is a significant relationship between facilitating condition variables with ease of use and perceived benefits. In addition, the results of this study illustrate a significant relationship between the core components TAM framework and will enrich the academic literature in understanding the conditions of learning platforms in the EdTech sector to support the needs of skills and competencies in the future.